Perancangan Sistem Pendukung Keputusan Untuk Menilai Kesiapan Siswa TK Dalam Masuk Sekolah Dasar Menggunakan Metode SAW Di TK Nurul Jannah - Agung Firmansyah; Nurhasanah (CV. Multi Kreasi Media, 2026)
The process of assessing kindergarten students' readiness for elementary school at Nurul Jannah Kindergarten is still done manually, resulting in subjective and inconsistent results. This study aims to develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to help teachers assess student readiness objectively and measurably. The system was developed using Extreme Programming (XP). This system uses five assessment criteria, which are then calculated through a process of normalization, weighting, and ranking. Implementation results indicate that the developed DSS produces more accurate, faster, and easier-to-understand assessments than manual methods, and assists teachers in determining student eligibility recommendations for elementary school entry